1997
DOI: 10.1016/s0959-4388(97)80008-6
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of utility estimation

Abstract: SummaryThe allocation of behavior among competing activities and goal objects depends on the payoffs they provide. Payoff is evaluated among multiple dimensions including intensity, rate, delay, and kind. Recent findings suggest that by triggering a stream of action potentials in myelinated, medial forebrain bundle axons, rewarding electrical brain stimulation delivers a meaningful intensity signal to the process that computes payoff.One asterisk following a reference number refers to a paper published within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 69 publications
(13 reference statements)
3
120
0
2
Order By: Relevance
“…Several authors have proposed that in order to integrate a disparate number of different rewards the brain uses a common network that converges in a final pathway that informs about the nature of the reward (comparison process) and about the possible courses of action in the future (Montague & Berns, 2002;Shizgal, 1997). Neurophysiological studies in animals revealed dopaminergic neurons in the midbrain projecting, among other regions, to the ventral striatum responding selectively to unpredicted events: (i) they are mostly responsive to appetetive events that are better than predicted, (ii) they do not respond to well-predicted rewards, and (iii) a negative signal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have proposed that in order to integrate a disparate number of different rewards the brain uses a common network that converges in a final pathway that informs about the nature of the reward (comparison process) and about the possible courses of action in the future (Montague & Berns, 2002;Shizgal, 1997). Neurophysiological studies in animals revealed dopaminergic neurons in the midbrain projecting, among other regions, to the ventral striatum responding selectively to unpredicted events: (i) they are mostly responsive to appetetive events that are better than predicted, (ii) they do not respond to well-predicted rewards, and (iii) a negative signal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Emotions as the common currency One of the essential insights of more than a half-century of research on reward and punishment is that animals reduce multidimensional alternatives to a single common currency that facilitates comparison and substitution (McFarland & Sibly 1975;Shizgal 1997;Montague & Berns 2002). While discussions of common currency within neuroscience typically '[make] no reference to hedonistic experience' (Shizgal 1997, p. 198), following Rolls (1999), we propose that emotion serves as the common currency with which humans make intertemporal trade-offs.…”
Section: Introduction: the Explicit Trade-off Perspectivementioning
confidence: 99%
“…First, the neural systems for approach-avoidance motivations have been shown to be lateralized: approach motivations are lateralized predominantly to the left hemisphere, whereas avoidance emotions are lateralized predominantly to the right hemisphere (44,45). Furthermore, electrical stimulation of different regions of the brain can unconditionally elicit approach and avoidance behavior (46)(47)(48)(49). For example, electrical stimulation of brain regions that receive projections from midbrain dopamine neurons-including the nucleus accumbens as well as mesial prefrontal cortex-elicits approach behavior.…”
mentioning
confidence: 99%